2021
DOI: 10.22159/ajpcr.2021.v14i2.40240
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health-Related Quality of Life and Risk Factors Associated With Pancreatitis in a Tertiary Care Hospital

Abstract: Objective: The objective of the study was to measure the health-related quality of life (HRQoL) in pancreatitis and to appraise the risk factors associated with the pancreatitis. Methods: A prospective observational study was performed with admitted cases of pancreatitis over 6 month’s period. A total of 150 patients were selected for the study. All data concerning risk factors were recorded and Short-Form-36 (SF-36) questionnaire was applied and quality of life (QOL) was analyzed in all patients with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 22 publications
2
6
1
Order By: Relevance
“…20 The incidence of alcoholic CP is higher in men, which is believed to be due to the differences in lifestyle between men and women. 12,20,[50][51][52] The present study did not find a relationship between sex and QoL in the analyzed domains of the SF-36 questionnaire. This is consistent with the findings from a number of other studies.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…20 The incidence of alcoholic CP is higher in men, which is believed to be due to the differences in lifestyle between men and women. 12,20,[50][51][52] The present study did not find a relationship between sex and QoL in the analyzed domains of the SF-36 questionnaire. This is consistent with the findings from a number of other studies.…”
Section: Discussioncontrasting
confidence: 86%
“…This finding is consistent with other studies where pain was found to be the only clinical variable having a negative impact on all the domains investigated in the SF-36 questionnaire. [4][5][6][7][8][10][11][12][13][14]33,34 Both the present study and other studies have shown that the intensity of pain is of key significance and that it is positively correlated with the degree of impairment of QoL. 6,11,33,34 The intensity of pain is of greater significance than its frequency.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations